IMPROVING POETRY WRITING SKILLS THROUGH THE WHEEL OF NAME MEDIA AT SMP NEGERI 4 JOMBANG ACADEMIC YEAR 2021/2022 - Susi Darihastining (Kantor Bahasa Provinsi Maluku Utara, 2023)
Based on observations made by researchers, it is known that the poetry writing skills of class VIII C students of SMP Negeri 4 Jombang are still less than the KKM score. The lack of students' ability to write poetry is caused by factors from teachers and students. The factor of the teacher is the lack of use of learning media because the teacher only uses the lecture method. Factors from students, namely students find it difficult to determine the theme as an object in developing their inspiration. This study aims to improve poetry writing skills using the Wheel of Name media in class VIII C students of SMP Negeri 4 Jombang. This study uses a model or method of classroom action research (CAR) from Kemmis & Taggart (Arikunto, 2010:137). This research was carried out in two cycles, cycle I and cycle II. The subjects of this study were students of class VIII C of SMP Negeri 4 Jombang as many as 31 students. Data was collected using test and non-test techniques. Non-test data obtained from observations, interviews, questionnaires and documentation. The test is in the form of an assessment of writing poetry with the assessment criteria, namely the choice of words/diction, rhyme/rhyme and language style/figurative language according to the theme. The results of this study indicate an increase in the average score of students' poetry writing in each cycle. Judging from the beginning of the activity, the pre-cycle has an average value of 68.70, increased in the first cycle with an average value of 76.12. Then from the average value of the first cycle 76.12 increased in the second cycle with an average value of 85.03. The increase was also marked by the presence of language styles used by students, namely personification, metaphor, hyperbole and sarcasm. Choice of words/diction and rhymes/rhymes that match the theme.